Moving towards the virtual state: integrating services and service channels for citizen-centred delivery - Kernaghan, Kenneth (2005)
Governments around the world are increasingly seeking to provide integrated, citizen-centred service delivery. The aim is to organize the delivery of services from the perspective of citizens rather than of governments and to deliver these services seamilessly across governments and across the delivery channels of the internet, the telephone and the service-counter. The four major categories of barriers to integrated service delivery are political/legal, structural, operational/managerial and cultural ones. The means of overcoming these barriers include such approaches as creating new service delivery models, perfecting partnerships, establishing an effective governance framework and providing dedicated funding. There are similar barriers - and similar solutions - to the challenge of integrated channel delivery. The challenge to integrating services and service channels becomes greater as initiatives move from the interdepartmental sphere to the interjurisdictional and intersector spheres. - Reproduced.
Keywords: Public administration